The road ahead : Middle East policy in the Bush administration's second term : planning papers - Leverett, Flynt Lawrence; Indyk, Martin (Brookings Institution, 2005)
This report from the Brookings Institution critiques the Bush Administration's performance in the Middle East. Seven essays by foreign policy experts describe alternative policy approaches aimed at better achieving U.S. goals in specific areas while promoting an integrated regional strategy. Four papers deal with U.S. policy towards specific countr.